Aligned nanofibres made of poly(3-hydroxybutyrate) grafted to hyaluronan for potential healthcare applications - Huerta-Ángeles, Gloria; Knotková, Kateřina; Knotek, Petr; Židek, Ondrej; Brandejsová, Martina; Pokorný, Marek; Vagnerová, Hana; Roy, Ipsita; Velebný, Vladimir (Journal of materials science. Materials in medicine, 2018)
In this work, a hybrid copolymer consisting of poly(3-hydroxybutyrate) grafted to hyaluronic acid (HA) was synthesised and characterised. Once formed, the P(3HB)-g-HA copolymer was soluble in water allowing a green electrospinning process. The diameters of nanofibres can be tailored by simply varying the Mw of polymer. The optimization of the process allowed to produce fibres of average diameter in the range of 100-150 nm and low polydispersity. The hydrophobic modification has not only increased the fibre diameter, but also the obtained layers were homogenous. At the nanoscale, the hybrid copolymer exhibited an unusual hairy topography. Moreover, the hardness and tensile properties of the hybrid were found to be superior compared to fibres made of unmodified HA. Particularly, this reinforcement was achieved at the longitudinal direction. Additionally, this work reports the use in the composition of a water-soluble copolymer containing photo cross-linkable moieties to produce insoluble materials post-electrospinning. The derivatives as well as their nanofibrous mats retain the biocompatibility of the natural polymers used for the fabrication.
Keywords: Polyesters; Hydrophobic and Hydrophilic Interactions; vstřebatelné implantáty; Tissue Scaffolds; Nanofibers; polymery; Absorbable Implants; Biocompatible Materials; Polymers; Hydroxybutyrates; nanovlákna; polyestery; tkáňové podpůrné struktury; Delivery of Health Care; kyselina hyaluronová; poskytování zdravotní péče; Equipment and Supplies; biokompatibilní materiály; biomechanika; hydroxybutyráty; Hyaluronic Acid; Biomechanical Phenomena; hydrofobní a hydrofilní interakce; zdravotnické prostředky